PENERAPAN MODEL INSIDE OUTSIDE CIRCLE (IOC) TERHADAP HASIL BELAJAR DI SMPN 1 LAMBU KABUPATEN BIMA - Nurfitrianingsih; Mustamin; Martini; Wahab, Abdul; Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve student learning outcomes in Islamic Religious Education and Character Education through the implementation of the Inside Outside Circle (IOC) learning model in class VIII.1 of SMP Negeri 1 Lambu, Bima Regency. The problem in this study is the low learning outcomes of students which is indicated by the large number of students who have not achieved the Minimum Completion Criteria (KKM) and the low student activeness in the learning process. This study uses the Classroom Action Research (CAR) method which is implemented in two cycles. Each cycle includes the stages of planning, action implementation, observation, and reflection. The research subjects were 36 students of class VIII.1 of SMP Negeri 1 Lambu. Data collection techniques were carried out through observation, learning outcome tests, interviews, and documentation. The results of the study indicate that the implementation of the Inside Outside Circle (IOC) learning model can improve student learning outcomes. In the initial conditions, only 9 students (25%) achieved learning completion, while 27 students (75%) had not achieved the KKM. After the implementation of the IOC model in Cycle I, the number of students who completed the learning increased to 23 people (63.89%) and those who had not completed it were 13 people (36.11%). In Cycle II, the learning completion rate increased again to 33 people (91.67%), while only 3 students (8.33%) had not completed it. In addition, the observation results showed an increase in student activity, participation, discipline, and enthusiasm during the learning process. Based on the results of the study, it can be concluded that the implementation of the Inside Outside Circle (IOC) learning model is effective in improving student learning outcomes in the subjects of Islamic Religious Education and Character Education for class VIII.1 of SMP Negeri 1 Lambu, Bima Regency.